Managerial Feedback, Associate Performance, and Eleven Positive Feedback Rules - Allen Wysocki; Karl Kepner (EDIS, 2002)
This is EDIS document HR 026, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published July 2002.